Enhance the Balance of Quadruped Robot using CMPS12 - Nasrulloh Azhar; Purno Tri Aji (Universitas Negeri Yogyakarta, 2023)
Quadruped is a robot that can move stably and flexibly on various types of surfaces. However, when quadruped encounters an uneven surface, it needs a good navigation system to get through it. The analysis of increasing the performance of the quadruped robot is based on the addition of the CMPS12 sensor for navigation. The CMPS12 sensor is used to measure the direction of the robot's orientation. Tests were carried out on four types of obstacles, namely broken road obstacles, sloping road obstacles, rocky road obstacles, and muddy road obstacles. The results of testing the robot on broken road obstacles obtained a maximum slope for the pitch axis of 13◦ forward, −21◦ to the rear and for the roll axis at a slope of 24◦ to the left and −19◦ to the right. On inclined road obstacles, the robot can pass through obstacles with an average travel time of 8.07 seconds with a maximum slope of 25◦ on the pitch axis. Then, on the rocky road obstacle, the robot can pass the obstacle with an average travel time of 8.13 seconds, with a maximum slope of 9◦ on the pitch axis and 8◦ on the roll axis. Then, on a muddy road obstacle, the robot can pass the obstacle with an average travel time of 11.67 seconds, with a maximum slope of 15◦ on the pitch axis and −6◦ on the roll axis.